Organoleptic Test Analysis of Pie Crust Using Rub-In and Blending Method - Cahyani, Vella Tri; Siregar, Juliana; Kasmita, Kasmita; Anggraini, Ezi (Universitas Negeri Padang, 2024)
This research was motivated by the discovery of different methods for making pies so it needed to be tested to see the quality produced using the rub-ib and blending methods. The aim of the research was to determine the comparison of pie crust quality using the rub-in and blending methods. This type of research is pure experiment using the Independent Sample T-test method. The research was carried out by providing an organoleptic test format to the panelists. The data obtained is then tabulated in table form and a level test is carried out on each variable X1 and X2 to find out whether there is a quality comparison for these variables. The results of the research show that there is no significant influence on the quality of the shape, color, aroma, texture and taste of the pie crust, for the quality of the shape (neat) it has an average value of X1 (2.77) and X2 (3.78), quality shape (uniform) X1 (4.00) and has an average of X1 (3.67) and X2 (3.78), while the average value for texture quality (dry) has an average of (crispy) has an average value of X1 (4.00) and X2 (3.67), finally for taste quality (savory) has an average value of X1 (4.00) and X1 (4.00).